Prognosticators of Visual Acuity After Indirect Traumatic Optic Neuropathy. Issue 2 (25th June 2022) - Wright, Alex J.; Queen, Joanna H.; Supsupin, Emilio P.; Chuang, Alice Z.; Chen, John J.; Foroozan, Rod; Adesina, Ore-Ofe O.
Abstract : Background: The purpose of this study is to determine whether there are radiographic and systemic clinical characteristics that can predict final visual outcomes in patients with indirect traumatic optic neuropathy (iTON). Methods: This study is a retrospective, multicenter case series of adult patients with iTON treated initially at large, urban, and/or academic trauma centers with follow-up at an affiliated ophthalmology clinic. In addition to detailed cranial computed tomography characteristics, demographics, systemic comorbidities, coinjuries, blood products administered, and intracranial pressure, along with other factors, were gathered. LogMAR visual acuity (VA) at the initial presentation to the hospital and up to 12 months follow-up was collected. Results: Twenty patients met inclusion criteria; 16 (80%) were men with a mean age of 40.9 years (±20.9). Mean initial VA was 1.61 logMAR (∼20/800, ± 0.95), and final VA was 1.31 logMAR (∼20/400, ± 1.06). Three patients (4 eyes) had no light perception (NLP) VA at presentation and remained NLP at final follow-up. Of the predictors analyzed, only the initial VA was found to be a significant predictor of visual outcome. The presence of orbital fractures, intraconal and/or extraconal hemorrhage, as well as systemic comorbidities, were not found to significantly affect visual outcome. Conclusions: After evaluating multiple factors, initial VA was the only factor associated with visual prognosis in iTON. This knowledge may better enable clinicians to predict visual prognosis and set reasonable expectations with patients and families at the time of injury.